2021
DOI: 10.1055/a-1361-4072
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy bei onkologischen Rehabilitanden und deren Relevanz für den subjektiven Rehabilitationsverlauf

Abstract: Zusammenfassung Ziel der Studie „Health literacy“ (HL) umfasst das Wissen, die Motivation und die Fähigkeiten von Menschen, gesundheitsrelevante Informationen zu finden, zu verstehen, zu beurteilen, anzuwenden und Entscheidungen bezüglich Gesundheitsfragen treffen zu können. Geringe HL ist mit gesundheitsbezogenen Verhaltensweisen und Gesundheit negativ assoziiert. Die explorative Studie untersucht die HL von onkologischen Rehabilitanden und deren Zusammenhang mit Reha-Zielparametern. Methodik Es erfolgte eine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Only one study suggested that patients with lower literacy needed deeper and more targeted support than the planned single intervention (Chambers et al, 2014 ). The importance of addressing health literacy in a self‐management intervention is documented in a German study, which described that at the end of an inpatient oncology rehabilitation, 56% of all patients reported limited health literacy (Meng et al, 2021 ). Health literacy was seen as a key point in the motivation and understanding of health information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study suggested that patients with lower literacy needed deeper and more targeted support than the planned single intervention (Chambers et al, 2014 ). The importance of addressing health literacy in a self‐management intervention is documented in a German study, which described that at the end of an inpatient oncology rehabilitation, 56% of all patients reported limited health literacy (Meng et al, 2021 ). Health literacy was seen as a key point in the motivation and understanding of health information.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy was seen as a key point in the motivation and understanding of health information. Higher health literacy has an impact on patients’ workability, their health status and the improvement of their rehabilitation outcomes (Meng et al, 2021 ). Lastly, no tendency was observed for studies with a higher quality to conduct more statistically significant results.…”
Section: Discussionmentioning
confidence: 99%
“…Work ability has been shown to be positively correlated with higher general health literacy ( 28 ), with nearly 20 percent of its variance explained by health literacy ( 29 ). In addition, limited health literacy has also been shown to contribute to social inequality and inequity in health ( 30–32 ).…”
Section: Introductionmentioning
confidence: 99%